A Comparison of the Immunostimulatory Effects of Polysaccharides from Tetraploid and Diploid Echinacea purpurea. (9th July 2018) - Yang, Guang; Li, Keke; Liu, Cui; Peng, Peipei; Bai, Mei; Sun, Jiaqi; Li, Qingling; Yang, Zhuohong; Yang, Yuesheng; Wu, Hong
Abstract : Polyploidization is an effective means of improving the active components and quality of secondary metabolism in medicinal plants. In the present study, we compared the immunostimulatory effects of crude polysaccharides from tetraploid and diploid Echinacea purpurea . The results showed that the carbohydrate contents of crude polysaccharide of tetraploid E. purpurea (CPE4) and diploid E. purpurea (CPE2) were 85.51% and 44.65%, respectively. 1 H-nuclear magnetic resonance (NMR) spectroscopy and gel-permeation chromatography (GPC) analyses showed no major differences in the overall structure and molecular weight of polysaccharides between CPE4 and CPE2. However, some differences in the relative content of the same polysaccharides group were observed between CPE4 and CPE2. In in vitro tests, EP4 could stimulate lymphocyte proliferation and secretion of cytokines maximally at the concentration of 0.0312 mg/mL, and EP2 could stimulate lymphocyte proliferation and secretion of cytokines maximally at the concentration of 0.125 mg/mL. In in vivo tests, EP4 was more effective at promoting the proliferation of lymphocytes and secretion of cytokines in mice immunosuppressed by cyclophosphamide than EP2 at the same concentration. Taken together, these data demonstrated that the relative content of the partial polysaccharides group is increased, and the immunoregulatory effect is enhanced in tetraploid E. purpurea .